Pressure flow field and inlet flow distortion metrics reconstruction from velocity data - Frascella, Michele; Zachos, Pavlos K.; Gil-Prieto, Daniel; MacManus, David G. (AIAA, 2016)
Complex engine intakes are susceptible to unsteady flow distortions that may compromise the propulsion system operability. Hence, the need for high spatial and temporal resolution flow information is essential to aid the development of distortion tolerant, closely coupled propulsion systems. Stereoscopic PIV methods have been successfully applied to these flows offering synchronous velocity datasets of high spatial resolution across the Aerodynamic Interface Plane. However, total pressure distortion measurements are still typically provided by low bandwidth, intrusive total pressure rakes of low spatial resolution which results in limited characterisation of the total pressure distortion. This limitation can potentially be addressed by pressure field reconstruction fromnon-intrusive, high resolution velocity data. A range of reconstruction methods are assessed based on representative data from steady and unsteady computational simulations of an Sduct configuration. In addition to the reconstructed total pressure field, the impact on the key distortion metrics is assessed. The effect of Mach number is considered. Overall the reconstruction methods show that the distortion metrics can be determined with sufficient accuracy to indicate that there is a potential benefit from exploiting high resolution velocity measurements in evaluating total pressure distortion.